Nivolumab in Advanced Hepatocellular Carcinoma: Safety Profile and Select Treatment‐Related Adverse Events From the CheckMate 040 Study. (24th August 2020) - Julien, Karen; Leung, Hiu Tung; Fuertes, Carmen; Mori, Megumi; Wang, Miao‐Jen; Teo, Jocelyn; Weiss, Lisa; Hamilton, Sara; DiFebo, Holly; Noh, Yoon Jin; Galway, Aralee; Koh, Jane; et al.
Abstract: Background: CheckMate 040 assessed the efficacy and safety of nivolumab in patients with advanced hepatocellular carcinoma (HCC). Understanding the safety profile of nivolumab is needed to support the management of treatment‐related adverse events (TRAEs). This analysis assessed the safety of nivolumab monotherapy in the phase I/II, open‐label CheckMate 040 study. Materials and Methods: Select TRAEs (sTRAEs; TRAEs with potential immunologic etiology requiring more frequent monitoring) occurring between first dose and 30 days after last dose were analyzed in patients in the dose‐ escalation and ‐ expansion phases. Time to onset (TTO), time to resolution (TTR), and recurrence of sTRAEs were assessed, and the outcome of treatment with immune‐modulating medication (IMM) was evaluated. Results: The analysis included 262 patients. The most common sTRAE was skin (35.5%), followed by gastrointestinal (14.5%) and hepatic (14.1%) events; the majority were grade 1/2, with 10.7% of patients experiencing grade 3/4 events. One patient had grade 5 pneumonitis. Median (range) TTO ranged from 3.6 (0.1–59.9) weeks for skin sTRAEs to 47.6 (47.1–48.0) weeks for renal sTRAEs. Overall, 68% of sTRAEs resolved, with median (range) TTR ranging from 3.7 (0.1–123.3+) weeks for gastrointestinal sTRAEs to 28.4 (0.1–79.1) weeks for endocrine sTRAEs. Most gastrointestinal and all hepatic events resolved with treatment in accordance with established toxicity management algorithms. In 57 patients (40%), sTRAEs were managed with IMM. Reoccurrence of sTRAEs was uncommon following rechallenge with nivolumab. Conclusion: Nivolumab demonstrated a manageable safety profile in this analysis of patients with advanced HCC. A majority of sTRAEs resolved with treatment. Abstract : The CheckMate 040 study assessed the efficacy and safety of nivolumab in patients with advance hepatocellular carcinoma. This article focuses on the safety of nivolumab monotherapy and associated treatment‐related adverse events.